Analysis of clinical characteristics of mirror and TV signs in Alzheimer's disease and dementia with Lewy bodies. Issue 2 (February 2023) - Chen, Gang; Liu, Shuai; Wu, Hao; Gan, Jinghuan; Wang, Xiaodan; Ji, Yong
Objective: This study explored the clinical features of dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) and analyzed the differences in neurologic syndromes, including mirror and TV signs, between different groups. Methods: Patients with AD and DLB (325 and 115, respectively) hospitalized in our institution were enrolled. We compared psychiatric symptoms and neurologic syndromes between the DLB and AD groups and within each subgroup, including the mild-moderate and severe subgroups. Results: The prevalence rates of visual hallucination, parkinsonism, rapid eye movement sleep behavior disorder, depression, delusion, and the Pisa sign were significantly higher in the DLB group than in the AD group. Furthermore, within the mild-moderate subgroup, the mirror sign and Pisa sign prevalence rates were significantly higher in the DLB group than in the AD group. In the severe subgroup, no significant difference was found in any neurologic sign between the DLB and AD groups. Conclusion: Mirror and TV signs are rare and often disregarded because they are not usually invoked during routine inpatient or outpatient interviews. According to our findings, the mirror sign is uncommon in early AD patients but common in early DLB patients and should receive increased attention.